Sorafenib dose escalation in treatment‐naïve patients with metastatic renal cell carcinoma: a non‐randomised, open‐label, Phase 2b study. (9th January 2017) - Gore, Martin E.; Jones, Robert J.; Ravaud, Alain; Kuczyk, Markus; Demkow, Tomasz; Bearz, Alessandra; Shapiro, JoAnn; Strauss, Uwe Phillip; Porta, Camillo
Abstract : Objective: To assess the efficacy and safety of sorafenib dose escalation in metastatic renal cell carcinoma (mRCC). Patients and Methods: Intra‐patient dose escalation may enhance the clinical benefit of targeted anticancer agents in metastatic disease. In this non‐randomised, open‐label, Phase 2b study, treatment‐naïve patients with mRCC were initially treated with the standard oral sorafenib dose [400 mg twice daily (BID)]. Two dose escalations were planned, each 200 mg BID after 28 days at the prior level. Dose reductions, interruptions, or delayed escalations were used to manage adverse events (AEs). The primary endpoint was objective response rate (ORR) in the modified intent‐to‐treat (mITT) population, which comprised patients with ≥6 months of treatment including ≥4 months of therapy at their highest tolerated dose. Secondary endpoints included progression‐free survival (PFS) and safety. Results: In all, 83 patients received sorafenib. The dose received for the longest duration was 400, 600, and 800 mg BID in 48.2%, 15.7%, and 24.1% of patients, respectively. The ORR was 44.4% [ n = 8/18; 95% confidence interval (CI) 21.5–69.2] and 17.9% ( n = 12/67; 95% CI 9.6–29.2) in the mITT and ITT populations, respectively. The median (95% CI) PFS was 7.4 (6.0–11.7) months (ITT). The most common AEs of any grade were hand–foot skin reaction (66.3%) and diarrhoea (63.9%). Conclusion: Sorafenib demonstrated clinical benefit in treatment‐naïve patients with mRCC. However, relatively few patients could sustain doses of >400 mg BID. There was evidence that, where tolerated, escalation from the standard sorafenib dose may have enhanced clinical benefit. However, this study does not support dose escalation for most patients with treatment‐naïve mRCC. Alternative protocols for sorafenib dose escalation could be explored.